Autism - Bardhan-Quallen, Sudipta (Detroit : Thomson/Gale ; Farmington Hills, MI : KidHaven Press, 2005)
Discusses the symptoms, treatments, and causes of autism, and explains some of the behaviors of people with autism.
What is autism? -- What are the symptoms of autism? -- Treating autism -- Living with autism -- Notes -- Glossary -- For further exploration -- Index -- About the author.
Includes bibliographical references (p. 40-41) and index.
Keywords: Autism -- Juvenile literature